Empowering Startup Company: Entrepreneurial Capacity as a Key Factor - Hayati, Nur; Jaelani, Evan; Ritonga, Duma Soswati (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: The startup sector continues to evolve amidst rising competition. Entrepreneurial leadership and artificial intelligence (AI) literacy are recognized as key enablers for sustaining and enhancing competitiveness. This study aims to explore how these two elements, both individually and in combination, influence the competitiveness of startup firms, with entrepreneurial capacity considered as a potential mediating factor.Methodology: The study employed a structural equation modeling approach using Partial Least Squares (PLS-SEM), drawing data from employees of digital startups based in West Java. Reliability and validity of the measurement model were confirmed through comprehensive statistical testing. The analysis assessed both direct and indirect relationships among variables.Result : The findings demonstrate that AI literacy exerts a strong and statistically significant positive influence on entrepreneurial capacity, as well as directly on startup competitiveness. Entrepreneurial leadership also shows a meaningful positive contribution to both entrepreneurial capacity and startup competitiveness. Furthermore, entrepreneurial capacity itself plays a crucial role in strengthening a startup’s market position and adaptability. The analysis confirms that entrepreneurial capacity serves as a significant mediating variable in the relationship between both AI literacy and entrepreneurial leadership with startup competitiveness. The overall model exhibits a high level of explanatory power, suggesting that the proposed variables collectively account for the vast majority of variance in startup competitiveness.Conclusion: The results underscore the importance of fostering AI literacy and entrepreneurial leadership within startup environments, as their impact on competitiveness is not only direct but also reinforced through enhanced entrepreneurial capacity. These findings provide practical guidance for startup leaders seeking to develop strategic capabilities and sustain growth in increasingly dynamic and tech-driven markets.